KARAKTERISTIK DAN PERTUMBUHAN KONSORSIUM MIKROBA LOKAL DALAM MEDIA MENGANDUNG MINYAK BUMI - Komarawidjaja, Wage (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Laboratory microcosm observation were conducted to study the effect of mediaculture containing oil spill in microbial growth ability . Laboratory microcosms wasinoculated with oil microbial consortia isolated from oil spill sample in Cepu oil field.Based on the colony characteristic differentiation, 5 microbial types identified fromthe sample. At the end of enrichment period and acclimatization on the BH mediacontaining 5% Cepu crude oil, all isolates as microbial consortia put into growthexperiment media.The experiment proved that microbes could be able utilizing oil as carbon sourcefor their cell multiplication. The results showed the more the turbidity concentrationincrease, the more the microbial population rise. These studies indicates thatreducing oil spill utilizing in situ bioremediation technologies can be realized